TLX1 (HOX11) Immortalization of Embryonic Stem Cell-Derived and Primary Murine Hematopoietic Progenitors - Hawley, Robert G. (2008)
The ability to generate genetically engineered cell lines is of great experimental value. They provide a renewable source of material that may be suitable for biochemical analyses, chromatin immunoprecipitation assays, structure-function studies, gene function assignment, and transcription factor target gene identification. This unit describes protocols for TLX1 (HOX11)-mediated immortalization of murine hematopoietic progenitors derived from in vitro differentiated murine embryonic stem cells, or from primary mouse fetal liver or bone marrow. A wide variety of hematopoietic cell types have been immortalized using these procedures including erythroid, megakaryocytic, monocytic, myelocytic, and multipotential cell types. These lines are typically cytokine dependent for their survival and growth.